Modelling Motor Insurance Claim Frequency and Severity Using Gradient Boosting - Clemente, Carina (2023)
Clemente, C., Guerreiro, G. R., & Bravo, J. M. (2023). Modelling Motor Insurance Claim Frequency and Severity Using Gradient Boosting. Risks, 11(9), 1-20. [163]. https://doi.org/10.3390/risks11090163 ---This research was funded by national funds through the FCT—Fundação para a Ciência e a Tecnologia, I.P., under the scope of the projects UIDB/00297/2020 and UIDP/00297/2020—Center for Mathematics and Applications—(G.R. Guerreiro) and grants UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC) and UIDB/00315/2020—BRU-ISCTE-IUL—(J.M. Bravo).